Lo no dicho / lo dicho: literatura cursi versus literatura comprometida según Belén Gopegui - Szymoniak, Ewelina (Romanica Silesiana)
<!--EndFragment--> Ewelina Szymoniak raises the issue of the engagement of the modern literature, presenting the two co-existing tendencies visible in the attitude of the Spanish writers, i.e. escapism from the reality in the name of the creative freedom and the conviction that leaving the up-to date social problems aside makes the writer guilty of being an accomplice to the abuse of the capitalistic system. Keywords: twentieth-century Spanish novel; literary commitment; a contemporary intellectual